Melatonin Improves the Fertilization Capacity of Sex-Sorted Bull Sperm by Inhibiting Apoptosis and Increasing Fertilization Capacitation via MT1 - Li, Chong-Yang; Hao, Hai-Sheng; Zhao, Ya-Han; Zhang, Pei-Pei; Wang, Hao-Yu; Pang, Yun-Wei; Du, Wei-Hua; Zhao, Shan-Jiang; Liu, Yan; Huang, Jin-Ming; Wang, Jing-Jing; Ruan, Wei-Min; et al. (International journal of molecular sciences, 2019)
Little information is available regarding the effect of melatonin on the quality and fertilization capability of sex-sorted bull sperm, and even less about the associated mechanism. Sex-sorted sperm from three individual bulls were washed twice in wash medium and incubated in a fertilization medium for 1.5 h, and each was supplemented with melatonin (0, 10−3 M, 10−5 M, 10−7 M, and 10−9 M). The reactive oxygen species (ROS) and endogenous antioxidant activity (glutathione peroxidase (GPx); superoxide dismutase (SOD); catalase (CAT)), apoptosis (phosphatidylserine [PS] externalization; mitochondrial membrane potential (Δψm)), acrosomal integrity events (malondialdehyde (MDA) level; acrosomal integrity), capacitation (calcium ion [Ca2+]i level; cyclic adenosine monophosphate (cAMP); capacitation level), and fertilization ability of the sperm were assessed. Melatonin receptor 1 (MT1) and 2 (MT2) expression were examined to investigate the involvement of melatonin receptors on sex-sorted bull sperm capacitation. Our results show that treatment with 10−5 M melatonin significantly decreased the ROS level and increased the GPx, SOD, and CAT activities of sex-sorted bull sperm, which inhibited PS externalization and MDA levels, and improved Δψm, acrosomal integrity, and fertilization ability. Further experiments showed that melatonin regulates sperm capacitation via MT1. These findings contribute to improving the fertilization capacity of sex-sorted bull sperm and exploring the associated mechanism.